Evaluation of musculoskeletal disorder Prevalence among students who use portable Computer in Qazvin Health College - mehran qhalenoy; sana shokri; bahram kohnavard (Mazandaran University of Medical Sciences, 2015)
Background The musculoskeletal disorders consist dominate part of occupational disease. Work with Portable Computer also can became one of the predominant cause of the musculoskeletal disorders. Therefore aim of this study was assessment of musculoskeletal disorders prevalence rate among portable computer using students and assessment of pain rate in different body regions and identify of more exposed organs. Methods This was a cross – sectional expression study that carry out on total students of the Qazvin Health collage (184 persons).To determine the prevalence of disorder from repetitive movements of the different organs of the body was used of kernel questionnaire as well as computer related musculoskeletal disorders questionnaire was used. Results Based on computer related musculoskeletal disorders questionnaire, most people felt pain in the right shoulder (23.9). Based on kernel questionnaires Upper arm, right neck, right hip and lower extremities, respectively, with 2/29% 3/30%, 2/8% have most pain. Conclusions Less using of tables and chairs for working with laptop is a common ergonomics problem among students. The use of tables and chairs for work with laptop and a using of external keyboard to reduce stress on the was proposed.